Time-scale effects in the interaction between a large and a small herbivore - Kuijper, D.P.J.; Beek, P.; van Wieren, S.E.; Bakker, J.P. (Basic and applied ecology, 2008)
In the short term, grazing will mainly affect plant biomass and forage quality. However, grazing can affect plant species composition by accelerating or retarding succession at longer time-scales. Few studies concerning interactions among herbivores have taken the change in plant species composition into account. In a salt-marsh system, the long-term effects of exclusion of a large herbivore (cattle) on the abundance of a small herbivore (hare) were studied. Excluding cattle grazing for 30 years resulted in large changes in vegetation composition. In general, the cover of tall-growing species increased in the absence of cattle grazing. These long-term changes negatively affected hare grazing intensity. Hares preferentially fed on Festuca rubra and negatively selected tall growing plants, such as Elymus athericus, both in cattle-grazed and long-term ungrazed areas. However, the intensity of hare grazing was not related to the cover of F. rubra. The cover of tall-growing plants ( E. athericus, Atriplex prostrata and Juncus maritimus) appeared to be the best predictor and hare grazing intensity decreased sharply with an increase of the cover of tall plants. When cover of tall plants did not increase, hare grazing intensity was not affected. The study shows that the time-scale of the experiment is of prime importance in studying interactions between herbivores. Species that do not seem to influence the abundance of one another or are competing for the same resources on a short time-scale might well be facilitating each other when looking at larger time-scales while taking plant species replacement into account. Kurzfristig wird die Beweidung vor allem die Pflanzenbiomasse und Nahrungsqualität beeinflussen. Beweidung kann jedoch auch die Zusammensetzung der Pflanzenarten beeinflussen, indem sie die Sukzession auf größeren Zeitskalen beschleunigt oder zurückhält. Wenige Untersuchungen, die die Interaktionen von Herbivoren betrachten, berücksichtigen die Veränderungen in der Pflanzenartenzusammensetzung. In einem Salzwiesensystem wurden die Langzeiteffekte des Ausschlusses von großen Herbivoren (Rinder) auf die Abundanz von kleinen Herbivoren (Hasen) untersucht. Der Ausschluss von Rinderbeweidung über 30 Jahre resultierte in großen Veränderungen in der Vegetationszusammensetzung. Generell nahm die Bodendeckung von hochwüchsigen Arten in Abwesenheit von Rinderbeweidung zu. Diese Langzeitveränderungen beeinflussten die Intensität der Hasenbeweidung negativ. Hasen fressen bevorzugt Festuca rubra und selektierten hochwüchsigen Pflanzen wie Elymus athericus sowohl in rinderbeweideten als auch langzeitig nicht beweideten Flächen negativ. Die Intensität der Hasenbeweidung stand jedoch in keinem Bezug zur Bodendeckung von Festuca rubra. Die Bodendeckung der hochwüchsigen Pflanzen ( Elymus athericus, Atriplex prostrata, Juncus maritimus) schien der beste Indikator zu sein und die Intensität der Hasenbeweidung nahm mit der Zunahme der Bodendeckung großer Pflanzen steil ab. Nahm die Bodendeckung großer Pflanzen nicht zu, wurde die Intensität der Hasenbeweidung nicht beeinflusst. Die Untersuchung zeigt, dass die Zeitskala des Experimentes von größter Bedeutung für die Untersuchung von Interaktionen zwischen Herbivoren ist. Arten, die ihre gegenseitigen Abundanzen nicht zu beeinflussen scheinen oder die auf einer kleinen Zeitskala um die gleichen Ressourcen konkurrieren, können sich gegenseitig durchaus fördern, wenn die Veränderungen in den Pflanzenarten auf größeren Zeitskalen berücksichtigt werden.